'TAM 204' Wheat, Adapted to Grazing, Grain, and Graze‐out Production Systems in the Southern High Plains. Issue 3 (1st September 2019) - Rudd, Jackie C.; Devkota, Ravindra N.; Ibrahim, Amir M.; Baker, Jason A.; Baker, Shannon; Sutton, Russell; Simoneaux, Bryan; Opena, Geraldine; Hathcoat, Daniel; Awika, Joseph M.; Nelson, Lloyd R.; Liu, Shuyu; et al.
Abstract : 'TAM 204' (Reg. no. CV‐1155, PI 686859), a hard red winter wheat ( Triticum aestivum L.) cultivar with the experimental designation of TX06V7266, was developed and released by Texas A&M AgriLife Research in 2014. TAM 204 is an F4 –derived line from the cross 'TAM 112'/TX01M5009 made at Vernon, TX, in 2001. TAM 204 is an apically awnletted, medium‐maturing, semidwarf wheat with red glumes. It was released primarily as a grain, dual‐purpose, and graze‐out wheat with high grain and forage yield potential. It has good acid soil tolerance, is resistant to Soil‐borne wheat mosaic virus, Wheat streak mosaic virus and its vector wheat curl mite, greenbug, stem rust and stripe rust, and it is moderately susceptible to leaf rust. TAM 204 has a high level of resistance to Hessian fly biotypes GP and vH9 and a moderate level of resistance to biotype vH13. Compared with 'TAM 111', which is currently the most widely grown cultivars in Texas, TAM 204 has significantly higher grain yield in the Texas High Plains under both irrigated and dryland environments. Compared with 'TAM 401' and 'Weathermaster 135', which are currently the two most popular apically awnletted cultivars in Texas, TAM 204 has similar forage yield but higher grain yield across a wide range of environments. TAM 204 could be a better option for wheat growers and cattle owners under grain‐only, dual‐purpose (grazing‐plus‐grain), and graze‐out production system in the southern US Great Plains.